COVID-19 Therapeutic Options Under Investigation - Kaddoura, Malak; AlIbrahim, Malak; Hijazi, Ghina; Soudani, Nadia; Audi, Amani; Alkalamouni, Habib; Haddad, Salame; Eid, Ali; Zaraket, Hassan (Frontiers in Pharmacology, 2020)
Since its emergence in China in December 2019, COVID-19 has quickly spread around the globe causing a pandemic. Vaccination or the development of herd immunity seems the only way to slow down the spread of the virus; however, both are not achievable in the near future. Therefore, effective treatments to mitigate the burden of this pandemic and reduce mortality rates are urgently needed. Preclinical and clinical studies of potential antiviral and immunomodulatory compounds and molecules to identify safe and efficacious therapeutics for COVID-19 are ongoing. Two compounds, remdesivir and dexamethasone, have been so far shown to reduce COVID-19-associated death. Here, we provide a review of the potential therapeutic agents being considered for the treatment and management of COVID-19 patients.